EFFECT OF STUDENT-INTERACTION PATTERNS ON STUDENTS’ ACADEMIC PERFORMANCE IN BASIC TECHNOLOGY IN EDO STATE SECONDARY SCHOOLS (Journal of Technology and Operations Management, 2020)
This study investigated the effect of student-interaction patterns on students academic performance in Basic Technology in Edo State junior secondary schools using non-equivalent control group quasi experimental research design. Two research questions and two null hypotheses guided the study. The study was conducted in Edo State. A sample size of 138 vocational II students was drawn using purposive sampling technique and used for the study. Three groups were used for this study; they are student-student interaction, student-teachers interaction and student material interaction patterns. The instrument for data collection was Basic Technology Achievement Test (BTAT). The research questions were answered using Mean and standard deviation while Analysis of Covariance (ANOVA) was used to test the hypotheses at .05 level of significance. Findings from the study revealed that there was significant mean effect of instructional strategies on students mean performance score in Basic Technology; there was no significant mean effect of gender on students’ Mean performance score in Basic Technology. In line with the findings of the study, the educational implication of the findings were highlighted and it was recommended among others that Basic Technology teachers should be trained on how best to involve students in student-student interaction patterns during instructions to facilitate students’ academic performance in the subject. This could be achieved through in-service training such as conferences, seminars and workshops for technical teachers.